Epithelioid glioblastoma with microglia features: potential for novel therapy. (6th August 2020) - Nakagomi, Nami; Sakamoto, Daisuke; Hirose, Takanori; Takagi, Toshinori; Murase, Makiko; Nakagomi, Takayuki; Yoshimura, Shinichi; Hirota, Seiichi
Abstract: Epithelioid glioblastoma (E‐GBM) was recently designated as a subtype of glioblastoma (GBM) by the World Health Organization (2016). E‐GBM is an aggressive and rare variant of GBM that primarily occurs in children and young adults. Although most characterized cases of E‐GBM harbor a mutation of the BRAF gene in which valine (V) is substituted by glutamic acid (E) at amino acid 600 (BRAF‐V600E), in addition to telomerase reverse transcriptase promoter mutations and homozygous CDKN2A/B deletions, the origins and cellular nature of E‐GBM remain uncertain. Here, we present a case of E‐GBM that exhibits antigenic and functional traits suggestive of microglia. Although no epithelial [e.g., CKAE1/3, epithelial membrane antigen (EMA)] or glial (e.g., GFAP, Olig2) markers were detected by immunohistochemical staining, the microglial markers CD68 and Iba1 were readily apparent. Furthermore, isolated E‐GBM‐derived tumor cells expressed microglial/macrophage‐related genes including cytokines, chemokines, MHC class II antigens, lysozyme and the critical functional receptor, CSF‐1R. Isolated E‐GBM‐derived tumor cells were also capable of phagocytosis and cytokine production. Treating E‐GBM‐derived tumor cells with the BRAF‐V600E inhibitor, PLX4032 (vemurafenib), resulted in a dose‐dependent reduction in cell viability that was amplified by addition of the CSF‐1R inhibitor, BLZ945. The present case provides insight into the cellular nature of E‐GBM and introduces several possibilities for effective targeted therapy for these patients.